Gender Perception on Entrepreneurial Literacy, Self-Efficacy on Entrepreneurial Intention through Entrepreneurial Attitude - Zainal Ruma; Dian Anggraece Sigit Parawansa; Muh Asdar; Fauziah Umar (Universitas 17 Agustus 1945 Semarang, 2024)
The highest unemployment rate is caused by graduates who have increased due to the available workforce being greater than the number of jobs available. The way to overcome unemployment is to increase entrepreneurial intentions. The purpose of this study was to investigate entrepreneurial intentions in students of the Faculty of Economics and Business, State University of Malang as it is believed that entrepreneurial intentions are the most important factor in entrepreneurial actions, using variables of entrepreneurial education, self-efficacy, gender, and entrepreneurial attitude variables as mediation. This research is a quantitative research using a descriptive research design. The dependent variable in this research is entrepreneurial intention (Y), the independent variable is entrepreneurial literacy (X1) and self-efficacy (X2) while the mediating variable is entrepreneurial attitude (Z). The population taken in this research is students. The sample taken in this research is 170 respondents calculated using the Slovin formula. The scale used in this is a Likert scale with 5 choices to be answered by the resource person, namely strongly disagree, disagree, disagree, agree, strongly agree. Furthermore, the instrument feasibility test uses validity and reliability tests. While the classical assumption test uses normality tests, multicollinearity tests, and heteroscedasticity tests. The analysis technique uses descriptive analysis, path analysis, sobel test and difference test. The results of this study indicate that entrepreneurship education on entrepreneurial intentions has a significant influence, self-efficacy on entrepreneurial intentions has a significant influence, entrepreneurship education on entrepreneurial intentions mediated by entrepreneurial attitudes has a significant influence, self-efficacy on entrepreneurial intentions mediated by entrepreneurial attitudes has a significant influence, entrepreneurial attitudes on entrepreneurial intentions have a significant influence and based on the results of the difference test